1989
DOI: 10.1016/0378-1097(89)90443-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of pathotypes of verocytotoxigenic Escherichia coli isolated from weaned piglets using gene probes for seven E. coli toxins

Abstract: Seventy verocytotoxigenic (VTEC) and sixty-three non VTEC haemolytic Escherichia coli isolated from recently weaned piglets were examined by the colony hybridization assay using gene probes for three verocytotoxins: Edema disease principle (EDP) and Shiga-like toxins I and II (SLTI and SLTII). The results with the EDP and SLTII probes were identical. All VTEC hybridized with these two probes, while non VTEC did not. All 133 E. coli were negative for the SLTI probe. Hybridization of the plasmid content of 14 VT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…These bacteria are considered to be normal inhabitants of the intestinal tract, with specific strains being an important cause of diarrhea. The etiology (25)(26)(27), epidemiology (21,30,32), and pathogenesis (6,33,39,40) of E. coli causing pre-and postweaning diarrhea in pigs have been the subject of many studies. However, there is relatively little information about the ecology and behavior of nonenteropathogenic E. coli throughout the animal's life.…”
mentioning
confidence: 99%
“…These bacteria are considered to be normal inhabitants of the intestinal tract, with specific strains being an important cause of diarrhea. The etiology (25)(26)(27), epidemiology (21,30,32), and pathogenesis (6,33,39,40) of E. coli causing pre-and postweaning diarrhea in pigs have been the subject of many studies. However, there is relatively little information about the ecology and behavior of nonenteropathogenic E. coli throughout the animal's life.…”
mentioning
confidence: 99%
“…However, the protocols usually require enrichment steps or overnight culture of isolated strains with the possibility of loss of enterotoxin gene sequences (14). In addition, problems with cross-hybridization of E. coli enterotoxin gene probes to unrelated or non-E. coli sequences have been described (20,23). In vitro DNA amplification of enterotoxin gene sequences by the highly specific polymerase chain reaction (PCR) overcomes these problems.…”
mentioning
confidence: 99%
“…VT1 and VT2 are cytotoxic to HeLa and Vero cells, whereas VTe is cytotoxic only to Vero cells (9). Although toxin-converting bacteriophages have been described for both VT1 and VT2, none have been isolated from VTe-producing porcine edema disease strains of E. coli, and the genes are likely chromosomal (8,9). Cloning and sequencing of the VT genes have been completed, and the A toxin subunit genes of VT2 and VTe were found to be highly homologous (94%), whereas the B toxin subunit genes were less homologous (79 to 80%) (3,14).…”
mentioning
confidence: 99%
“…Although most DNA hybridization probes described to date have failed to differentiate VT2-and VTe-producing VTEC (1,5,8,10,11), variation in the degrees of stringency has permitted identification of E. coli isolates producing VT2 and VTe at 53°C but not at 45°C (1). Using these probes, Brown et al reported VTe-producing isolates of E. coli associated with human disease, thereby suggesting a possible pathogenic role for VTe in humans (1).…”
mentioning
confidence: 99%